Mn−O Covalency Governs the Intrinsic Activity of Co‐Mn Spinel Oxides for Boosted Peroxymonosulfate Activation. (27th October 2020) - Guo, Zhi‐Yan; Li, Chen‐Xuan; Gao, Miao; Han, Xiao; Zhang, Ying‐Jie; Zhang, Wen‐Jun; Li, Wen‐Wei
Abstract: Transition metal (TM)‐based bimetallic spinel oxides can efficiently activate peroxymonosulfate (PMS) presumably attributed to enhanced electron transfer between TMs, but the existing model cannot fully explain the efficient TM redox cycling. Here, we discover a critical role of TM−O covalency in governing the intrinsic catalytic activity of Co3− x Mn x O4 spinel oxides. Experimental and theoretical analysis reveals that the Co sites significantly raises the Mn valence and enlarges Mn−O covalency in octahedral configuration, thereby lowering the charge transfer energy to favor MnOh –PMS interaction. With appropriate Mn IV /Mn III ratio to balance PMS adsorption and Mn IV reduction, the Co1.1 Mn1.9 O4 exhibits remarkable catalytic activities for PMS activation and pollutant degradation, outperforming all the reported TM spinel oxides. The improved understandings on the origins of spinel oxides activity for PMS activation may inspire the development of more active and robust metal oxide catalysts. Abstract : The Mn−O covalency was enlarged by the Co sites mainly in the octahedral configuration, which results in a decreased charge transfer energy to favor Mn–PMS interaction and enhance Mn IV reduction to boost PMS activation activity of Co‐Mn spinel oxides.